Enjoying fermented fruit beverages - Garg, Neelima; Kumar, Sanjay; Yadav, Preeti (Indian Horticulture, 2019)
With the growing health awareness among masses in the modern world, consumption of fruits and their products is increasing as they are rich in vitamins, flavanoids, fibres and minerals. As a result, processed food market, the world over, is flooded with various kinds of fruit products like purees, jams, jellies, juices, nectars, RTS beverages, candies, preserves, etc. Fermentation using Saccharomyces cerevisiae yeast is a traditional way of fruit preservation. However, fermented fruit beverages other than grape wine and apple cider are not yet available commercially in the market. Keeping in this view, scientists of Central Institute for Subtropical Horticulture, Lucknow, have developed a number of fermented fruit beverages with characteristic fruity aroma and taste. Unlike liquors, which contain high amount of alcohol with no nutritional benefit, these beverages are better suited to health due to presence of good amount of vitamins and anti-oxidants.